Intentions to use maternity waiting homes and associated factors in Northwest Ethiopia - Mekonen Endayehu; Mezgebu Yitayal; Ayal Debie (BMC, 2020)
Abstract Background Maternity Waiting Homes (MWHs) are residential facilities located within hospitals or health centers to accommodate women in their final weeks of pregnancy to bridge the geographical gap in obstetric care. Little is known, however, about women's intentions to use MWHs. Thus, this study aimed to assess pregnant women's intentions to use MWHs and associated factors in East Bellesa district, northwest Ethiopia. Methods A community-based cross-sectional study was conducted among 525 pregnant women in East Bellesa district from March to May 2018. Study participants were selected using systematic random sampling. Binary logistic regression was used for analysis. Adjusted Odds Ratio (aOR) with 95% Confidence Interval (CI), and p-value < 0.05 were used to identify factors associated with intentions to use MWHs. Results In the study area, 326/499 (65.3%) pregnant women had the intention to use MWHs. Pregnant women who had good knowledge about maternal healthcare and obstetric complications (aOR 6.40; 95% CI 3.6-11.5), positive subjective norms related to women's perceptions of social pressure (aOR 5.14; 95% CI 2.9-9.2), positive perceived behavioral control of women on the extent to which women feel confident (aOR 4.74; 95% CI 2.7-8.4), rich wealth status (aOR 4.21; 95% CI 2.1-8.4), women who decided by themselves to use maternal services (aOR 2.74; 95% CI 1.2-6.2), attended antenatal care (aOR 2.24; 95% CI 1.2-4.1) and favorable attitudes towards women's overall evaluation of MWHs (aOR 1.86; 95% CI 1.0-3.4) had higher odds of intentions to use MWHs. Conclusion Two thirds (65.3%) of pregnant women had intentions to use MWHs. Factors such as women's knowledge, subjective norms related to women's perceptions of social pressure, perceived behavioral control of women on the extent to which women feel confident to utilize, and wealth status, decision-making power, attending antenatal care and attitude towards women's overall evaluation of MWHs were significantly associated with the intention to use MWHs. Therefore, improving women's awareness by providing continuous health education during antenatal care visits, devising strategies to improve women's wealth status, and strengthening decision-making power may enhance their intention to use MWHs.